Bio-etiek sonder grense: ʼn Verkenning en Christelik-etiese beoordeling van die UNESCO universele deklarasie van bio-etiek en menseregte (2005) - Rheeder, Riaan (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
It is clear that the world community realized the need for a Declaration on bio-ethics and human rights. It led to an assignment given by the member states to UNESCO to develop a declaration. During the development of the declaration many stakeholders were involved in a transparent process, which led to the approval of the declaration unanimously by all 191 member states, in 2005. The strength of this declaration is found in the fact that for the first time in human history, mankind is united regarding bio-ethical principles as a form of human rights and is therefore morally committed to compliance with the ethos of the declaration. This declaration may be particularly valuable in developing countries because in general a bio-ethical infrastructure is lacking. Christians do not need to feel uncomfortable about global or universal ethical principles, because there is enough evidence in their writings to support universal ethics, as long as the principles do not clash with principles found in Scripture.